2012
DOI: 10.1310/sci1802-106
|View full text |Cite
|
Sign up to set email alerts
|

Motor and Gait Improvement in Patients With Incomplete Spinal Cord Injury Induced by High-Frequency Repetitive Transcranial Magnetic Stimulation

Abstract: Objective:To assess the effect of high-frequency repetitive transcranial magnetic stimulation (rTMS) on lower extremities motor score (LEMS) and gait in patients with motor incomplete spinal cord injury (SCI). Method: The prospective longitudinal randomized, double-blind study assessed 17 SCI patients ASIA D. We assessed LEMS, modified Ashworth Scale (MAS), 10-m walking test (10MWT), Walking Index for SCI (WISCI II) scale, step length, cadence, and Timed Up and Go (TUG) test at baseline, after the last of 15 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
136
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(148 citation statements)
references
References 13 publications
3
136
0
9
Order By: Relevance
“…To date, three studies of this type have been published related to walking, [16][17][18] as well as a case study related to lower extremity muscle activity. 120 Two studies using transcranial direct current stimulation (tDCS) followed by locomotor training showed mixed results.…”
Section: Targeting Supraspinal Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, three studies of this type have been published related to walking, [16][17][18] as well as a case study related to lower extremity muscle activity. 120 Two studies using transcranial direct current stimulation (tDCS) followed by locomotor training showed mixed results.…”
Section: Targeting Supraspinal Structuresmentioning
confidence: 99%
“…17 In a study of repetitive TMS (rTMS) applied over the leg motor area in persons with American Spinal Injury Association Impairment Scale (AIS) D injury classification, 17 subjects were randomized to either rTMS or sham-tTMS. 18 Both groups also received locomotor training. The study concluded that rTMS was associated with improvements in walking speed, lower extremity motor scores, and spasticity that were not observed in the sham-rTMS group.…”
Section: Field-fote Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…For example, PAS pulse pairs are delivered once every 5 s. Repetitive TMS (rTMS) without concomitant PNS can have positive effects in incomplete SCI patients for 2-3 weeks; 11,12 however, in SCI patients, high-intensity TMS is needed to effectively activate the corticospinal tract, 13 and long-term use of high-frequency and high-intensity rTMS may be contraindicated for SCI patients with head injury, as rTMS reduces the seizure threshold. 13,14 In contrast, PAS utilizes less risky low-frequency TMS.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] Studies of rTMS and transcranial direct cortical stimulation are also based on patients with preserved voluntary activity in the muscles under investigation. 11,12,18 PAS induces plasticity in humans without concomitant effort by the subject; 4 we thus hypothesized that long-term PAS could be a technique that could affect also those muscles which are fully paralyzed.…”
Section: Introductionmentioning
confidence: 99%